2019
DOI: 10.1002/env.2606
|View full text |Cite
|
Sign up to set email alerts
|

Bayesian inference for finite populations under spatial process settings

Abstract: We develop a Bayesian model–based approach to finite population estimation accounting for spatial dependence. Our innovation here is a framework that achieves inference for finite population quantities in spatial process settings. A key distinction from the small area estimation setting is that we analyze finite populations referenced by their geographic coordinates. Specifically, we consider a two‐stage sampling design in which the primary units are geographic regions, the secondary units are point‐referenced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…Cooper (2006) reviews the two approaches in an ecological context before introducing a 'model-assisted' variance estimator that combines aspects from each approach. In addition to Cooper (2006), there has been substantial research and development into estimators that use both design-based and model-based principles (see e.g., Sterba (2009) and Cicchitelli and Montanari (2012), and for Bayesian approaches, see Chan-Golston et al (2020) and Hofman and Brus (2021)).…”
Section: Introductionmentioning
confidence: 99%
“…Cooper (2006) reviews the two approaches in an ecological context before introducing a 'model-assisted' variance estimator that combines aspects from each approach. In addition to Cooper (2006), there has been substantial research and development into estimators that use both design-based and model-based principles (see e.g., Sterba (2009) and Cicchitelli and Montanari (2012), and for Bayesian approaches, see Chan-Golston et al (2020) and Hofman and Brus (2021)).…”
Section: Introductionmentioning
confidence: 99%
“…Recent work includes a method for block kriging which connects geostatistical models and classical design-based sampling (Hoef, 2002), a spline-based estimator of the mean for samples drawn from a spatially-correlated population (Cicchitelli & Montanari, 2012), and the use of linear spatial interpolator to create a design-based predictor of values at unobserved locations (Bruno et al, 2013). Chan-Golston et al (2020) demonstrated that accounting for both design and spatial association in a two-stage sampling context led to better model fit and better coverage of the finitepopulation parameters.…”
Section: Introductionmentioning
confidence: 99%
“…To illustrate, we turn to nitrate concentration data collected in wells in California. Note that these data are discussed and analyzed more thoroughly in Section 5 and similar data were analyzed in Chan-Golston et al (2020). The population data consist of approximately 7000 wells in central California.…”
Section: Introductionmentioning
confidence: 99%